Market valuation analysis for selected companies in healthcare industry / Nurhaslinda Hashim, Munirah Mohamed and Siti Daleela Mohd Wahid - Hashim, Nurhaslinda; Mohamed, Munirah; Mohd Wahid, Siti Daleela (2023)
The COVID-19 pandemic was characterized as a global phenomenon by the WHO in March 2020. The pandemic had significant effects, short and long-term impacts on healthcare companies and the healthcare industry. Hence, healthcare companies should analyze their financial performance to sustain themselves in this critical period. For that reason, this paper aims to comprehend how selected companies in the healthcare industry utilize all the components in a company’s financial statement to achieve outstanding company performance. Our analysis used market valuation ratios such as earnings per share (EPS) and book value per share (BVPS). To strengthen our analysis, we determine the strengths and weaknesses to assess the healthcare companies’ position in the market. Thus, we will recommend strategies that will aid the company in better performance in the future.